Learning numbers to 99 - Sinclair, Karleen; Anderson, Greg; Heather, Warwick (Cairo Dar el farouk, 2004)
In this book , students will learn to count and write numbers up to 99they will learn how to break up groups of objects into groups of 10 , then count the extras to form numbers to99
Mathematics
8 12 13
Keywords: Mathematics